INFORMATION ABOUT ARCHITECTURAL MONUMENTS CREATE AND MAINTAIN A BANK - Khusanova Mashhura Islamovna; Omonov Ismail Kholboevich; Rakhmatillaeva Kamola Boratovna (International Engineering Journal For Research & Development, 2020)
One of the most important tasks is the study and preservation of architectural monuments of state importance, the ability to reflect the cultural heritage of the people, its way of life